Establishing and Sustaining a Culture of Collegial Collaboration. Issue 6 (2nd July 2020) - McAllister, Alex M.; Wiglesworth, Lesley; Wilson, John H.
Abstract : Creating a cohesive team of coworkers can be challenging in any organization, and an academic department is no exception. The Centre College Mathematics Department has established a culture of collegial collaboration by investing in developing a strong mathematical community of faculty and students, and through careful attention to the hiring and mentoring of new faculty members. This article discusses our approach to creating and maintaining this culture in the midst of several transitions in leadership and personnel as well as multiple modifications to our curriculum and major. While the Centre College Mathematics Department is a relatively small group working at a liberal arts college, many of these ideas can be readily adapted to and implemented in departments of varying sizes and types.